2005
DOI: 10.1007/s10096-005-1312-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of measuring serum procalcitonin, C-reactive protein, and mannan antigens to distinguish fungal from bacterial infections

Abstract: The study presented here was conducted to determine the diagnostic value of measuring procalcitonin, C-reactive protein, and mannan antigens to distinguish fungal from bacterial infections. The sensitivity and specificity of these measurements ranged from 35% to 97%. On days 1 and 3 following the onset of fever, both serum procalcitonin and C-reactive protein levels were lower in patients with fungal infections than in those with bacterial infections (p<0.0001). The presence of mannan antigens combined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…For example, Peltola and coworkers [22] have shown that two consecutive C-reactive protein ≤20 mg/L can largely exclude the possibility of invasive bacterial infection both in immunocompetent and immunocompromised hosts. Another prospective study of hospitalized patients, found that C-reactive protein levels were lower in those with fungal infections than in those with bacterial infections [23]. Our data confirmed these previous findings that a lower C-reactive protein response is associated with IFI than with M. tuberculosis or other bacterial infections in SLE patients.…”
Section: Discussionsupporting
confidence: 94%
“…For example, Peltola and coworkers [22] have shown that two consecutive C-reactive protein ≤20 mg/L can largely exclude the possibility of invasive bacterial infection both in immunocompetent and immunocompromised hosts. Another prospective study of hospitalized patients, found that C-reactive protein levels were lower in those with fungal infections than in those with bacterial infections [23]. Our data confirmed these previous findings that a lower C-reactive protein response is associated with IFI than with M. tuberculosis or other bacterial infections in SLE patients.…”
Section: Discussionsupporting
confidence: 94%
“…10e15,17 Several other studies have reported lower PCT levels in patients with fungal than in those with bacterial infections. 18,19,21 Distefano et al compared PCT and CRP levels in low birthweight infants 21 ; PCT levels were significantly lower in babies with fungal than in those with bacterial infections. Petrikkos and co-workers first evaluated serum PCT levels in fungal infections 18 and then the power of PCT and mannan antigen to distinguish fungal from bacterial infection.…”
Section: Discussionmentioning
confidence: 96%
“…Several investigators [32,34] have reported normal PCT levels at the onset of fungal infections with subsequent increases in patients with higher severity of illness. Petrikkos et al [51] measured serum PCT, CRP, and mannan antigens in 91 neutropenic, human immunodeficiency virus (HIV) infected, critically ill patients with fungal and bacterial infection. CRP and PCT levels were higher in patients with bacterial infection than in those with fungal infection on the first and the third day after the onset of infection.…”
Section: Value Of Pct According To the Infecting Micro-organismmentioning
confidence: 99%